The contribution of the accuracy of spatial tracking of moving objects to the competitive efficiency of hockey defenders 13-15 years old - Tsepelevich, M. M.; Okuneva, A. S.; Savin, D. N.; Golovanova, I. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to quantify the contribution of the accuracy of spatial tracking of moving objects to the effectiveness of the competitive activity of hockey defensemen aged 13-15.